Revisiting the frequency domain: the multiple and partial coherence of cerebral blood flow velocity in the assessment of dynamic cerebral autoregulation. (31st May 2016) - Katsogridakis, Emmanuel; Simpson, David M; Bush, Glen; Fan, Lingke; Birch, Anthony A; Allen, Robert; Potter, John F; Panerai, Ronney B
Abstract: Despite advances in modelling dynamic autoregulation, only part of the variability of cerebral blood flow velocity (CBFV) in the low frequency range has been explained. We investigate whether a multivariate representation can be used for this purpose. Pseudorandom sequences were used to inflate thigh cuffs and to administer 5% CO2 . Multiple and partial coherence were estimated, using arterial blood pressure (ABP), end-tidal CO2 (EtCO2 ) and resistance area product as input and CBFV as output variables. The inclusion of second and third input variables increased the amount of CBFV variability that can be accounted for ( p   <  10 −4 in both cases). Partial coherence estimates in the low frequency range (<0.07 Hz) were not influenced by the use of thigh cuffs, but CO2 administration had a statistically significant effect ( p   <  10 −4 in all cases). We conclude that the inclusion of additional inputs of a priori known physiological significance can help account for a greater amount of CBFV variability and may represent a viable alternative to more conventional non-linear modelling. The results of partial coherence analysis suggest that dynamic autoregulation and CO2 reactivity are likely to be the result of different physiological mechanisms.